Struktur Histologi Hepar Tikus Wistar (Rattus norvegicus) Jantan setelah Pemberian Teh Kombucha Konsentrasi 75% dengan Waktu Fermentasi yang Berbeda - Isdadiyanto, Sri; Tana, Silvana (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
This research was conducted to study and analyze the influence of kombucha fermentation 6 (P1), 9 (P2) and 12 (P3) days fermentation with 75% concentration on hepatic tissue structure and hepatocyte diameter. This study used 16 male Wistar rats consisted of 4 treatments and 4 repeat. The treatment of this study consisted of P0: control treatment; P1, P2 and P3 were treatment of kombucha fermented tea 6, 9 and 12 days of 75% concentration respectively. This research used Completely Randomized Design (RAL). The variables measured in this study were hepatocyte diameter, body weight, feed and drink consumption in animal test. The data obtained were analyzed using Analysis of Variance (ANOVA) at 95% confidence level. The result of data analysis showed that kombucha fermentation 6, 9 and 12 days of 75% concentration had no significant difference to all variables. Histology of the liver were not indicate the presence of tissue-damaged features such as chronic inflammation (cirrhosis). It could be concluded that tea kombucha was safe for consumption by mammalia because it was not affect liver damage.